Plant nematology - Perry, Roland N.; Moens, Maurice (CABI Pub., 2006)
This book on plant parasitic nematodes contain 16 chapters classified under the following headings: taxonomy and principal genera (chapters 1-6), nematode biology and plant responses (chapters 7-10), and quantitative nematology and management (chapters 11-16). This book will be of importance as an advanced textbook for senior undergraduates and postgraduates in crop protection and nematology.